Gibbs energy function: Difference between revisions
Jump to navigation
Jump to search
Carl McBride (talk | contribs) m (New page: Definition: :<math>\left.G\right.=A+pV</math> :<math>\left.G\right.=U-TS+pV</math> Taking the total derivative :<math>\left.dG\right.=dU-TdS-SdT+pdV+Vdp</math> but from equation \ref...) |
Carl McBride (talk | contribs) mNo edit summary |
||
Line 10: | Line 10: | ||
:<math>\left.dG\right.=dU-TdS-SdT+pdV+Vdp</math> | :<math>\left.dG\right.=dU-TdS-SdT+pdV+Vdp</math> | ||
From the [[Second law of thermodynamics]] one obtains | |||
:<math>\left.dG\right.=TdS -pdV-TdS-SdT+pdV+Vdp</math> | :<math>\left.dG\right.=TdS -pdV-TdS-SdT+pdV+Vdp</math> |
Revision as of 18:10, 22 February 2007
Definition:
Taking the total derivative
From the Second law of thermodynamics one obtains
thus one arrives at
For G(T,p) we have the following total differential
Good for $NpT$